Evaluation of the Tuberculosis Control Program at the Bandar Lampung City Satellite Inpatient Community Health Center - Hasrita Ekasari, Yenni; -, Adinda (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2024)
Data from the Tuberculosis Information System (SITB) for the TB program estimates that there will be 6,559 new cases of tuberculosis (TB) in Bandar Lampung City in 2022. The Satellite Inpatient Community Health Center identified 842 suspected cases, with 147 cases notified, and 142 treated. The tuberculosis treatment success rate at the Satellite Inpatient Community Health Center is 97%. The purpose of this study was to evaluate the Tuberculosis Control Program at the Bandar Lampung Satellite Inpatient Community Health Center in Bandar Lampung City. This study used qualitative research methods, using an evaluation study to assess the ongoing or past program. Data was collected and compared against TB control standards. The research subjects were interviewed with key informants, primary informants, and triangulation informants. The informant selection technique used purposive sampling. The research was conducted from July 2023 to December 2024. The results of the study were obtained from all information obtained during the research process, including input factors (human resources, TB control methods, funding, equipment and infrastructure), process factors (planning, activity implementation, and reporting), output factors (treatment success rate, suspect screening, treatment success rate, and community participation), outcome factors, and impact factors. The conclusion of this study is the evaluation of the implementation of the TB program at the Satellite Inpatient Community Health Center (Puskesmas Rawat Sat) based on each of the input, process, output, outcome, and impact factors of the TB control program.